A compact and highly isolated integrated 8-port MIMO antenna for sub-6 GHz and mm-wave 5G-NR applications - Manumula Srinubabu; Nuthakki Venkata Rajasekhar (Results in Engineering)
This article presents a compact, self-coupled 8-port MIMO antenna design with enhanced isolation for sub-6 GHz and mm-wave bands in 5G-NR applications. The design features a novel elliptical-shaped monopole antenna with a CPW-fed structure for sub-6 GHz frequencies. These antennas are symmetrically arranged and extended into a 4-port MIMO configuration. By etching a triangular shape with a diagonal length of 15 mm at each corner of the substrate, the 4-element MIMO antenna achieves a 45° orientation to the axis. This modification reduces the antenna's size, creates space for mm-wave band antennas, enhances spatial diversity, and improves port isolation. Additionally, the design includes four symmetrical semi-circular monopole antennas with circular slits for mm-wave frequencies. The integrated 8-port MIMO antenna merges both sub-6 GHz and mm-wave designs on a single FR-4 substrate (εr = 4.5, tanδ = 0.002) with optimized spacing, maintaining a compact size of 70x70x1.2 mm3. The antenna achieves a bandwidth of 2.2 GHz (Sxx < -10 dB), covering 3.15–5.35 GHz for sub-6 GHz applications, and 6.7 GHz (Sxx < -10 dB), spanning the 23.20–29.90 GHz band for mm-wave frequencies. The antenna demonstrates excellent isolation and gain, with S21 values below -25 dB and peak gains of 11.75 dBi and 12 dBi for the sub-6 GHz and mm-wave bands, respectively. It also exhibits strong diversity performance, with an envelope correlation coefficient8x8 of 0.004 and efficiencies ranging from 88% to 96% for the respective frequency bands. The antenna's stable radiation patterns and spatial diversity make it well-suited for 5G-NR, Wi-Fi 6, and V2X applications.